Impact of high-intensity interval and moderate-intensity continuous exercise on heart rate variability and cardiac troponin - Huang, C.; Kong, Z.; Nie, J.; Pan, M.; Zhang, H.; Shi, Q.; George, K. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: It remains uncertain whether exercise modality (high-intensity interval [HIE]; moderate-intensity continuous [MCE]) mediates exercise-induced changes in markers of pro-arrhythmogenic state and/or cardiac damage. This study examines heart rate variability (HRV) and cardiac troponin T (cTnT) kinetic responses to HIE and MCE. METHODS: Fourteen sedentary, overweight/obese females completed two trials including HIE (2-min running at 90% VO2max followed by 2-min running at 50% VO2max, repeated for 60 min) and MCE (70% VO2max steady-state running for 60 min) in a randomized, counterbalanced fashion. Supine HRV was evaluated as root mean square of successive differences (RMSSD), normalized low-frequency (LF) and high-frequency (HF) spectral power, as well as the LF/HF ratio before (PRE), immediately (0 HR), 3 (3 HR) and 24 (24 HR) hours after exercise. Serum cTnT was assessed using a high-sensitivity assay at the same time-points and the values were corrected for plasma volume changes. RESULTS: Exercise temporarily altered all HRV indices (i.e. RMSSD and HF decreased; LF and LF/HF ratio increased at 0 HR, all P<0.05) but a rebound increase of RMSSD was observed at 24 HR, and the kinetic responses of HRV were similar between exercise modalities. The cTnT was significantly elevated (P<0.05) after exercise at 3 HR (by 688%) and 24 HR (by 374%) with no between-modality differences. There was no significant correlation between delta change in cTnT and HRV metrics. CONCLUSIONS: Exercise modality (workload-equivalent HIE vs. MCE) did not mediate exercise-induced alteration in autonomic activity and cTnT elevation, and it seems these are largely separate exercise-induced phenomena.